2004
DOI: 10.1152/japplphysiol.00202.2004
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor and related molecules in acute lung injury

Abstract: VEGFs and their receptors have been implicated in the regulation of vascular permeability in many organ systems, including the lung. Increased permeability and interstitial and pulmonary edema are prominent features of acute lung injury (ALI)/acute respiratory distress syndrome (ARDS). Extrapolating data from other organ systems and animal experiments have suggested that overexpression of VEGF functions primarily as proinjurious molecules in the lung. Recent data, from animal models as well as from patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
157
1
13

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(177 citation statements)
references
References 150 publications
6
157
1
13
Order By: Relevance
“…ALI/ARDS is characterized by alveolar injury and increased pulmonary vascular permeability. Mura et al (22) reported a potential role for VEGF in promoting the repair of the alveolar-capillary membrane during recovery from ALI/ARDS. Vegfb is associated with the VEGF signaling pathway and is involved in the promotion of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…ALI/ARDS is characterized by alveolar injury and increased pulmonary vascular permeability. Mura et al (22) reported a potential role for VEGF in promoting the repair of the alveolar-capillary membrane during recovery from ALI/ARDS. Vegfb is associated with the VEGF signaling pathway and is involved in the promotion of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is a well-known vascular permeability factor. 1,9,47 VEGF can reduce transendothelial electrical resistance, induce endothelial migration 5 as well as phosphorylation of VE-cadherin and E-cadherin, and alter the actin stress fibers in pulmonary endothelial cells. 6 Using a ventilated pulmonary ischemia model in isolated ferret lungs, it has been shown that pulmonary vascular barrier dysfunction is associated with a rapid increase in VEGF expression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the chemotactic activity of VEGF may contribute to monocyte activation and migration. 9 Lack of type II epithelial cell-derived VEGF may reduce the recruitment of inflammatory cells into the lung. Our results strongly support the hypothesis that VEGF locally produced in the distal lung epithelial cells is important for the pathogenesis of ALI/ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…10), among others. Indeed, the levels of these chemical factors are elevated in lung epithelial lining fluid collected from patients with early phase of ARDS, and they seem to have a key role in the pathogenesis of this disease 11,12 . The present study was initiated based on the recent finding that VEGF-induced angiogenesis can be regulated by changes in the mechanical properties (for example, physical compliance) of the extracellular matrix (ECM), which also has a central role in control of stem cell fate switching and tissue development, as well as cancer formation [13][14][15][16] .…”
mentioning
confidence: 99%